Kepercayaan Masyarakat Terhadap Kebudayaan Grebeg dalam Tinjauan Pendidikan Islam - Nabila Hafizhotul Millah; Fauzyah Anindhya Mafazah; Nida Adilah Rahma; Nurgita Raihana Sulti (AR-RASYID : Jurnal Pendidikan Agama Islam, 2022)
Islamic culture in the archipelago provides a perspective and impact on the beliefs of each individual. This study aims to determine the Islamic culture in the Central Java region against this tradition. This study uses a descriptive qualitative method in providing an overview of the topic under study. The sample population in this study were two residents of Central Java who had followed the grebeg culture in their neighborhood. The instruments used are online interviews via zoom meetings and literature collection from several related sources. The results of this study are that Grebeg culture is a cultural tradition that has been passed down from generation to generation by the local area to the next by giving blessings to the surrounding community and people's belief that the implementation of Grebeg culture is a form of gratitude to Allah SWT for the blessings that have been given in the form of produce.